EVALUASI TINGKAT KEPUASAN PASIEN TERHADAP PELAYANAN DOKTER DI PUSKESMAS SUNGAI LILIN KABUPATEN MUSI BANYUASIN DALAM RANGKA PELAKSANAAN SISTEM ASURANSI KESEHATAN BPJS - Mayumi Gultom, Venny (Jurnal Kesehatan dan Pembangunan, 2025)
Every individual, regardless of social status or economic ability, has the same right to receive quality healthcare services. The objective of this research is to determine the level of satisfaction with doctor services in healthcare facilities within the BPJS health insurance system. The approach used in this study is a quantitative approach with explanatory research type. The research was conducted by the researcher at all Puskesmas in Sungai Lilin District, Musi Banyuasin Regency. The sample in this study consisted of 120 respondents. The research results show that the quality of doctor services has an impact on the satisfaction level of BPJS users. This means that the more positive the patients' perception of the quality of doctor services, the more their satisfaction tends to increase. However, the quality of doctor services does not have a significant impact on the BPJS implementation system, so changes in patients' perceptions of doctor quality do not affect the system. On the other hand, the BPJS implementation system has been proven to affect patient satisfaction; the better the patients' view of the BPJS implementation system, the higher their satisfaction level will be. The quality of doctor services and the implementation system of BPJS both influence patient satisfaction, but the quality of doctor services does not affect the BPJS implementation system.